2014
DOI: 10.1002/lpor.201300215
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the radiation direction of propagating surface plasmons on silver nanowires

Abstract: Metal nanowires supporting propagating surface plasmons (SPs) can be used as nanowaveguides and nanoantennas for light manipulation beyond the diffraction limit. Here the control of the propagation and radiation of SPs on silver nanowires is investigated. By covering an Al 2 O 3 layer onto a silver nanowire to change the local dielectric environment, the wave vector of the propagating SPs is increased. Thus, the radiation direction of SPs into the substrate is changed according to the phase matching condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 45 publications
0
85
0
Order By: Relevance
“…The inner ring represents the critical angle where the total internal reflection occurs, hence the bright areas inside this inner ring are due to the direct transmission of the light through the dielectric multilayer. On the BFP images, the bright vertical line labelled with SPP is the signature of the SPP propagating along the Ag NW [32], and the line is parallel to the axis Kx/K0, which is perpendicular to the NW long axis. From the distance (D) between this vertical line and the axis (Kx/K0), the diameter of the outer ring (R) and known NA (1.49) of the objective, the effective refractive index (or wavenumber, or the real part of the propagation constant) β/K0 of this SPP waveguide mode can be calculated with the equation β/K0 = (D/R)*NA, where the K0 is the wavenumber of the light in vacuum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inner ring represents the critical angle where the total internal reflection occurs, hence the bright areas inside this inner ring are due to the direct transmission of the light through the dielectric multilayer. On the BFP images, the bright vertical line labelled with SPP is the signature of the SPP propagating along the Ag NW [32], and the line is parallel to the axis Kx/K0, which is perpendicular to the NW long axis. From the distance (D) between this vertical line and the axis (Kx/K0), the diameter of the outer ring (R) and known NA (1.49) of the objective, the effective refractive index (or wavenumber, or the real part of the propagation constant) β/K0 of this SPP waveguide mode can be calculated with the equation β/K0 = (D/R)*NA, where the K0 is the wavenumber of the light in vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…β/K 0 is the effective refractive index of the plasmonic mode, and the imaginary part (β') represents the propagation loss. Details of image formation on the FFP and BFP, and how to derive the embedded optical information from the BFP and FFP images, can be found in references [29][30][31][32][33]. The silver nanowire (Ag NW) was placed on a dielectric multilayer consisting of alternating layers of SiO2 (105-nm-thick) and Si3N4 (88-nm-thick).…”
Section: Methodsmentioning
confidence: 99%
“…Basic optical properties of propagating SPs have been carried out. It was found that the Fabry-Pérot resonances of the forward-and backward-propagating plasmons on the nanowires generate directional emission from the nanowire waveguide [18,127]. The directional emission is also observed by the technique of back confocal Fourier imaging [34].…”
Section: Nanoantenna and Waveguiding Effects On Sersmentioning
confidence: 95%
“…Many structures have been proposed as plasmonic waveguides [64][65][66][67]; among these, chemically synthesized metal NWs show superior performances due to their crystalline structure which results in low propagation loss [67,68]. Intensive studies into SP propagation on individual metal NWs have been performed, which reveals the fundamental properties of nanowire SPs, for example the emission direction, propagation loss and group velocity of SPs [22,69]. Complex NW structures and networks can be built by assembling individual metal NWs.…”
Section: Metal Nanowire Network For Sp Guiding and Routingmentioning
confidence: 99%